CULTIVATION OF SWEET PEPPER (Capsicum annuum L.) TRANSPLANTS UNDER HIGH PRESSURE SODIUM LAMPS SUPPLEMENTED BY LIGHT-EMITTING DIODES OF VARIOUS WAVELENGTHS - Aistė Bagdonavičienė; Aušra Brazaitytė; Akvilė Viršilė; Giedrė Samuolienė; Julė Jankauskienė; Ramūnas Sirtautas; Sandra Sakalauskienė; Jurga Miliauskienė; Nijolė Maročkienė; Pavelas Duchovskis (Acta Scientiarum Polonorum: Hortorum Cultus, 2015)
In greenhouses, artificial lighting is applied in winter and early spring as supplementary light source to increase photosynthesis and plant growth. The objective of this study was to evaluate the cultivation of sweet pepper transplants under LED lamps that were developed to supplement HPS lamps used in greenhouses. The experiments were carried out in the greenhouses at the Lithuanian Research Centre for Agriculture and Forestry Institute of Horticulture. Sweet peppers (Capsicum annuum) L. cultivar ‘Reda’ and the hybrid ‘Figaro’ F1 were used for investigation. Four types of solid-state lamps were used with light-emitting diodes (LEDs) with peak emissions at blue 455 nm and 470 nm, cyan 505 nm, and green 530 nm. PPFD of each type of LED lamp was 15 μmol m-2 s-1, and the PPFD of HPS lamps was 90 μmol m-2 s-1. The reference transplants were grown under the illumination of HPS lamps (110 μmol m-2 s-1). The photoperiod of artificial lighting was maintained at 18 hours. Our experiments revealed different responses to supplemental LED lightings between the cultivar and the hybrid. The supplemental 470 nm illumination with HPS lamps mostly resulted in increases in the following areas: leaf area, fresh and dry weight, and the photosynthetic pigment content of the sweet pepper ‘Reda’ transplants. A similar positive effect was determined using supplemental 455 and 505 nm LED lights. However, the supplemental green 530 nm LED lights had no effect on growth, and they inhibited the development of the sweet pepper ‘Reda’ transplants. The HPS light had a positive effect on the growth parameters of the ‘Figaro’ F1 transplants, but all of the supplemental LED lights suppressed their growth and development.